Efek minyak ikan terhadap histopatologi hati mencit yang diinduksi dengan azoksimetan dan dekstran sodium sulfat: Effect of fish oil on the histopathology of liver in mice induced by azoxymethane and dextran sodium sulfate - Wangi, Surya Buana; Syofyan, Stephen Dario; Kusmardi , Kusmardi (Jurnal Pengolahan Hasil Perikanan Indonesia, 2024)
Death from colorectal cancer is generally caused by damage to the human liver through metastasis. Fish oil has anti-inflammatory and immunomodulatory effects, which can reduce liver damage. The treatment of colorectal cancer has been studied in vivo in mice. The purpose of this study was to determine the optimal dose of fish oil for liver damage in mice by measuring the number of necrotic foci, steatosis, inflammation, dysplasia, and obstructed central veins. Fish oil is produced from the fins, stomach contents, and heads of tuna fish, which are by-products of the filleting industry, and is then extracted with papain. The fin pulp, stomach contents, and heads of tuna were mixed with papain at 85% and 15%, respectively. Experimental mice were divided into four groups: without fish oil, low-dose fish oil (1.5 mg/day), medium-dose (3 mg/day), and high-dose (6 mg/day). The four groups received treatment in the form of AOM induction at 10 mg/kg BW and DSS 2% (w/v). The parameters analyzed included the number of necrotic foci, steatosis, inflammation, dysplasia, and obstructed central veins. The results showed that different fish oil doses affected the number of necrotic foci and central vein obstruction in the levers of the mice. The extent of steatosis, inflammation, and dysplasia was not observed in the levers of the mice by microscopic observation. The best treatment was the administration of high-dose fish oil (6 mg/day) because it could reduce necrotic foci and central vein obstruction in the lever of mice by 24.40±3.29 units and 4.20±2.28 units. Oil from tuna fish (Thunnus albacares) can improve the histopathology of the levers of mice induced by AOM and DSS.